Chapter 1 Decomissioning Monuments, Mobilizing Materialities - Rigney, Ann (Taylor & Francis, 2023)
Chapter 1: New memories emerge in relation to old ones. This means that undermining the power of hegemonic narratives is as crucial a part of memory activism as is the bringing of hitherto occluded histories into visibility. This point is made by reference to the many ways in which public monuments have long become the target of protestors and the destruction of monuments a key feature of regime change. The very material presence of monuments explains why they can cause offense, but also why they provide a platform and a location for practicing dissent. The article ends by surveying the different strategies that can be deployed in order to change the meaning of existing monuments so as to bring about mnemonic change.